2005
DOI: 10.1007/s11120-005-4118-z
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and Kinetic Analysis of the Energy Coupling in the PS I–LHC I Supercomplex from the Green Alga Chlamydomonas reinhardtii at 77 K

Abstract: Energy transfer processes in the chlorophyll antenna of the PS I-LHCI supercomplexes from the green alga Chlamydomonas reinhardtii have been studied at 77 K using transient absorption spectroscopy with multicolor excitation in the 640-670 nm region. Comparison of the kinetic data obtained at low and room temperatures indicates that the slow approximately approximately 100 ps excitation equilibration phase that is characteristic of energy coupling of the LHCI peripheral antenna to the PS I core at physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
3
24
1
Order By: Relevance
“…This is in line with the biochemical data presented in our manuscript. Using time-resolved absorption spectroscopy at 77K, Melkozernov et al [55] identified two distinct red spectral pools which belong to low-energy pigments in LHCI that absorb at 687 and 697 nm. These low energy pigments might be coordinated by Lhca4 and the Lhca2 and Lhca9 which have an asparigine (N) residue at position A5 that is involved in the formation of red chlorophyll clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the biochemical data presented in our manuscript. Using time-resolved absorption spectroscopy at 77K, Melkozernov et al [55] identified two distinct red spectral pools which belong to low-energy pigments in LHCI that absorb at 687 and 697 nm. These low energy pigments might be coordinated by Lhca4 and the Lhca2 and Lhca9 which have an asparigine (N) residue at position A5 that is involved in the formation of red chlorophyll clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that Lhca4 and Lhca9 are induced under iron-deficiency in C. reinhardtii, which would thereby increase the number of red chlorophylls per PSI-LHCI [41]. Since LHCI is uncoupled from PSI during iron deficiency, the fast energy transfer route through gap chlorophylls to the PSI core is severed (as is the case at low temperatures [55]) which decreases delivery of excitation energy to P700 while increasing delivery of exitation energy to non light harvesting carotenoids which results in photoprotective energy loss [49]. In addition, our results suggest that the population of PSI-LHCI in C. reinhardtii is heterogeneously composed with differing LHCI composition which implies heterogeneity in energy transfer routes within PSI-LHCI.…”
Section: Discussionmentioning
confidence: 99%
“…Such interpretation may be supported by the recent results of Drop and co-workers, who showed that Lhca2 and Lhca9, two algal LHCI monomers present in the PSI-LHCI complex in the 1:1 ratio with the core, are only loosely associated with it [7]. Melkozernov and co-workers also found that in the kinetic data obtained at 77 K the slow~100-ps excitation equilibration phase is not observed and stated that at low temperatures the LHCI antenna system is energetically uncoupled from the PSI core [57]. In turn, Ihalainen and co-workers suggested that the long-lived phase cannot be due to "slow" energy transfer, and they assigned it to an unrelaxed state of the pigment-protein complex that, on this time-scale, is converted into the final emitting state [56].…”
Section: Origin Of the Slow Fluorescence Decaymentioning
confidence: 95%
“…This suggests that some equilibration process between the most blue-shifted chlorophylls and the longer-wavelengths chlorophylls centered at ~ 685 nm has occurred on a time-scale shorter than the time-resolution of the experiment, i.e., shorter than 3.5 ps. Streak camera measurements do not allow for a direct observation of this downhill energy transfer, but comparison of RT and 77 K initial signals shows clearly that this process is much more efficient at 77 K. Such a fast equilibration processes occurring with a lifetime of ~ 0.5 ps was observed previously for the PSI core from C. reinhardtii in time-resolved absorption measurements (pump-probe) at RT (Gibasiewicz et al 2001), at 77 K (Melkozernov et al 2005) and at 10 K (Gibasiewicz et al 2002), after excitation between 650 and 680 nm, and was also more efficient in low-temperature measurements. The slowest component is described by the decay time of 5.3 ns and a DAS maximum at 675 nm ( Fig.…”
Section: Psi Corementioning
confidence: 73%